Panji beyond Java: narrative transformation in the Andi-Andi oral art of South Kalimantan - Sulisno Sulisno; Sunarto Sunarto; Suwardi Endraswara; Widodo Widodo (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2026)
The Panji stories have spread widely from East Java to various parts of Southeast Asia, but their transformation in indigenous oral traditions outside the royal cultural centers remains understudied. This article examines the transformation of Panji narrative elements in the oral art of Andi-andi in the Dayak people of the Meratus Mountains and the Dayak Bakumpai around the Barito River. Using a qualitative approach through ethnographic documentation, narrative transcription, and comparative literary analysis of Andi-andi stories featuring characters such as Bungsu Kaling, Angkau Melayu, and Galuh Mendam Jinaman, this study integrates theoretical perspectives of cultural diffusion, narrative mobility, and performativity. The findings identify three main transformation processes: cosmological relocation from the Javanese royal sphere to the sacred landscape of the Meratus Mountains and the Barito River valley; character indigenization through the replacement of Panji and Candrakirana with local ancestral figures; and performative ritualization, where the narrative is embedded in local ritual practices and spiritual systems. Rather than preserving the Panji story textually, the Andi-andi tradition rearticulates its narrative ethos of wandering, separation, and reunion within local cosmologies and collective memory, illustrating how classical narratives are continually reinterpreted through the storytelling traditions of indigenous peoples in South Kalimantan.